REVIEW OF TASYRĪ' PHILOSOPHY ON QABŪL REPRESENTATION IN MARRIAGE IN PALLANGGA DISTRICT, GOWA REGENCY - Idrus, Achmad Musyahid; Mukarromah, Nurul Faatikhatul; Ramli, Arif Rahman; Nurdin, Roswati; Abdul Qayyum, Abdul Rahman Hi (Al-Risalah, 2023)
This study aims to analyze and explore the philosophical aspects of the concept of Tasyri' in the context of Kabul representation in marriage, especially in Pallangga District, Gowa Regency. Tasyri' is an approach to Islamic law that covers various aspects of life, including marriage law. Kabul representation, as the guiding principle of marital property, has its roots in the philosophical views underlying Islamic law. This research uses a qualitative approach with textual analysis methods to explore a deep understanding of Tasyri's philosophical views regarding Kabul representation. The data was collected through in-depth interviews with religious leaders, Islamic jurists, and communities in Pallangga sub-district. In addition, primary sources such as Islamic law books and related literature are also used as references to support the analysis. The results showed that Kabul's representation in marriage had a deep philosophical basis in Tashri's view. This principle reflects aspects of equality, justice, and responsibility in the marital relationship. This philosophical view provides the foundation for the application of marriage law that accommodates individual and family interests in a balanced manner. In the context of Pallangga sub-district, Kabul representation still has relevance and is applied in marriage practice. However, there are also social and cultural dynamics that influence the interpretation and implementation of this principle. The study concludes that understanding Tasyri's philosophical views on Kabul representation can provide deeper insight into the cultural roots and values that shape the practice of marriage law in the society